2012
DOI: 10.3892/or.2012.1823
|View full text |Cite
|
Sign up to set email alerts
|

Altered microRNA expression in cisplatin-resistant ovarian cancer cells and upregulation of miR-130a associated with MDR1/P-glycoprotein-mediated drug resistance

Abstract: microRNAs (miRNAs) are short non-coding RNA molecules which are involved in the regulation of various biological processes. Drug resistance has become a major obstacle to successful chemotherapy of ovarian cancer. The aim of this study was to investigate microRNA expression profiles in cisplatin-resistant ovarian cancer cells and the role of miR-130a in regulating drug resistance. Analysis of differentially expressed miRNAs between SKOV3 and SKOV3/CIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 43 publications
(48 reference statements)
1
68
0
Order By: Relevance
“…There were no significant differences between the two groups in terms of gender, age, international prognostic index (IPI) and stage. We investigated the pretreatment concentrations of serum miR-155, miR-200c, miR-29c, miR-130a, miR-145, miR-451, miR-125b and miR-21 expression levels, which have been reported in certain other tumor types to be associated with chemotherapy resistance (Table III) (9,14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). We observed that only the expression of miR-130a and miR-125b was correlated significantly with the response to chemotherapy.…”
Section: Dysregulated Expression Profiles Of Eight Mirnas In Dlbclmentioning
confidence: 90%
See 2 more Smart Citations
“…There were no significant differences between the two groups in terms of gender, age, international prognostic index (IPI) and stage. We investigated the pretreatment concentrations of serum miR-155, miR-200c, miR-29c, miR-130a, miR-145, miR-451, miR-125b and miR-21 expression levels, which have been reported in certain other tumor types to be associated with chemotherapy resistance (Table III) (9,14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). We observed that only the expression of miR-130a and miR-125b was correlated significantly with the response to chemotherapy.…”
Section: Dysregulated Expression Profiles Of Eight Mirnas In Dlbclmentioning
confidence: 90%
“…A number of previous studies have revealed that miRNAs are involved in the progress of drug resistance in certain types of cancer (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). These miRNAs might play a crucial role in drug resistance by targeting their specific genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But the role of miR-130a in cancer drug resistance remains controversial. Yang et al [26] found that downregulation of miR-130a could inhibit MDR1 mRNA and P-gp expression, and overcome the cisplatin resistance in SKOV3/CIS cells. In this study, we found that miR-130a was down-regulated in the cisplatin-resistant A2780/DDP cells when compared with its corresponding cisplatinsensitive parental cell lines by qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Garofalo et al (2012) found that some miRNAs, such as miR-221, miR-222, and miR-30, are associated with gefitinib resistance in NSCLC cell lines by targeting the proteins which contribute to drug resistance. Some researchers have also shown that miR-130a contributes to multidrug resistance in human hepatocellular carcinoma (HCC) and ovarian cancer (Xu et al, 2012;Yang et al, 2012). However, to date there have been no reports concerning the role of miR-130a in gefitinib resistance in NSCLC.…”
Section: Introductionmentioning
confidence: 99%